SISTEM INFORMASI PENJUALAN KREDIT PADA MOHAN GROSIR SOLO SECARA MULTIUSER - Riwi Astuti, Bebas Widada, Andriani Kusumaningrum (STMIK Sinar Nusantara, 2017)
Mohan Grosir Solo is a store engaged in the field of Sales and Sales Cooperation Sales with Credit Sales System. Sales of credit that runs from direct submission to the cashier by submitting identity cards only. Customers do the taking of goods in accordance with the value of the approved filing then the customer will pay in accordance with the applicable provisions. With the credit sales information system is expected small errors up to the large can be resolved, especially the problem of payment arrears and repayment payment. System design that includes: Diagram Context, HIPO, Data Flow Diagrams, Document Flow Diagrams, Database Design, Input Design, Output Design, Implementation of the program by using appropriate data stimulation. The purpose of this research is to create and design multi-level loan sales information system at Mohan Grosir Solo. Then the results obtained from this system are Input of Goods Data, Input of Customer Data, Input of Supplier Data, Input of Data of Department of Goods, Input of Cashier Data, Purchase Transaction, Purchase Return Transaction, Credit Sale Transaction, Sales Return Transaction, Cash Transaction, Customer Data Report, Supplier Data Report, Department of Goods Data Report, Cashier Data Report, Purchase Transaction Report, Purchase Return Report, Credit Sales Transaction Report, Sales Returns Report, and Cash Advance Report. System information created using Microsoft Visual Basic 6 and SQL Server database has been done blackbox testing with a design that is appropriate. Keywords: Information System, Multiuser, Credit Sales.